Oncologic Surveillance After Radical Nephroureterectomy for High-risk Upper Tract Urothelial Carcinoma - Martini, Alberto; Lonati, Chiara; Nocera, Luigi; Fallara, Giuseppe; Raggi, Daniele; Herout, Roman; Zamboni, Stefania; Ploussard, Guillaume; Predere, Benjamin; Mattei, Agostino; Simeone, Claudio; Krajewski, Wojciech; et al. (European urology oncology, 2022)
BACKGROUND: The appropriate surveillance protocol after radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC) is still poorly addressed. OBJECTIVE: To evaluate the appropriate intensity and duration of oncologic surveillance following RNU, according to a prior history of bladder cancer (BCa). DESIGN, SETTING, AND PARTICIPANTS: We identified 1378 high-risk UTUC patients, according to the European Association of Urology (EAU) guidelines, from a prospectively maintained database involving eight European referral centers. Surveillance protocol was based on cystoscopies and cross-sectional imaging, as per the EAU guidelines. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: First, we evaluated the noncumulative risk of bladder and other-site recurrences (including distant metastasis and locoregional relapse) against the follow-up time points, as suggested by the current EAU guidelines. Second, in an effort to identify the time points when the risk of other-cause mortality (OCM) exceeded that of recurrence and follow-up might be discontinued, we relied on adjusted Weibull regression. RESULTS AND LIMITATIONS: The median follow-up was 4 yr. A total of 427 and 951 patients with and without a prior BCa history, respectively, were considered. At 5-yr, the time point after which cystoscopies should be performed semiannually, the bladder recurrence risk was 10%; at 4 yr, the bladder recurrence risk was 13%. At 2 yr, the time point after which imaging should be obtained semiannually, the nonbladder recurrence risk was 42% in case of nonprior BCa and 47% in case of prior BCa; at 4 yr, the nonbladder recurrence risk was 23%. Among patients without a prior BCa history, individuals younger than 60 yr should continue both cystoscopies and imaging beyond 10 yr from RNU, 70-79-yr-old patients should continue only imaging beyond 10 yr, while patients older than 80 yr might discontinue oncologic surveillance because of an increased risk of OCM. Limitations include the fact that patients were treated and surveilled over a relatively long period of time. CONCLUSIONS: We suggest intensifying the frequency of imaging to semiannual till the 4th year after RNU, the time point after which the risk of recurrence was almost halved. Cystoscopies could be obtained annually from the 4th year given a similar risk of recurrence at 4 and 5 yr after RNU. Oncologic surveillance could be discontinued in some cases in the absence of a prior BCa history. PATIENT SUMMARY: In this study, we propose a revision of the current guidelines regarding surveillance protocols following radical nephroureterectomy. We also evaluated whether oncologic surveillance for high-risk upper tract urothelial carcinoma could be discontinued and, if so, in what circumstances.
Keywords: Bladder recurrence; karcinom z přechodných buněk; Upper tract urothelial carcinoma; nádory močovodu; Neoplasm Recurrence, Local; Nephroureterectomy; lidé; nefroureterektomie; retrospektivní studie; Radical nephroureterectomy; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; nádory močového měchýře; Distant recurrence; Ureteral Neoplasms; lokální recidiva nádoru; Urothelial cancer; Ureter; ureter; Follow-up; Retrospective Studies; Humans